TINGKAT PENGETAHUAN CLEAN SPORT – DOPING PADA SISWA/I SMP KELAS VIII PEMBANGUNAN LABORATORIUM UNP: THE LEVEL OF CLEAN SPORT–DOPING KNOWLEDGE AMONG EIGHTH-GRADE STUDENTS OF SMP PEMBANGUNAN LABORATORIUM UNP - muharani, nabila; Muharani, Nabila; Effendi, Hastria; Susanto, Nugroho; Selviani , Iit (Jurnal IKEOR, 2026)
This study aims to determine the level of students’ knowledge regarding clean sport related to doping among eighth-grade students at SMP Pembangunan Laboratorium UNP. The background of this research is based on the limited understanding among students about the concept of clean sport, the dangers of doping, and the lack of optimal integration of anti-doping material in physical education learning. This study employed a descriptive method with a quantitative approach. The sample consisted of 29 students selected using a purposive sampling technique. The instrument used was a questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive percentage techniques. The results of the study indicate that the level of students’ knowledge falls into the “good” category (96.6%), with an average score of 93.8%. These findings suggest that, in general, students possess a good level of knowledge regarding clean sport and doping. Keywords: knowledge, clean sport, doping, students, teenagers